Bank Reconciliation Process Efficiency Using Online Web Based Accounting System 2.0 in Companies - Sunarya, Po Abas; Nurhaeni, Tuti; Haris, Haris (APTISI Transactions on Management (ATM), 2017)
In the company the development of technology and knowledge which is marked by various advances in the field of communication and information technology is currently developing so rapidly. Clear information is information that presents data that is very accurate and complete and has benefits for the recipient of information or the leader of the company in monitoring. one of them is in the financial field within the company. In the current era of globalization an online computerized system becomes a very important requirement because it can reduce bad things and risk losing important data, difficulty in reconciliation like total bill not balance. therefore the web-based online accounting system provides Cash & Bank facilities so it can be reconciled both traditionally and modernly to facilitate in the process of bookkeeping of financial statements and certainly very effective because it does not require a long time, so effective and efficient.